Circulating endothelial precursor cells (EPC) in patients undergoing allogeneic haematopoietic progenitor cell transplantation - Pytlík, R; Kideryová, L; Benesová, K; Cechová, H; Veselá, R; Rychtrmocová, H; Trnený, M (Folia biologica, 2010)
We have studied the number of endothelial precursor cells in eighteen patients undergoing allogeneic haematopoietic stem cell transplantation. Endothelial precursor cells were evaluated by colony-forming assay and compared to healthy controls. Patients undergoing allogeneic haematopoietic stem cell transplantation had significantly lower numbers of endothelial precursor cells before the procedure than healthy controls. The numbers of endothelial precursor cells were even lower in the first year after the treatment and seemed to recover partially after twelve months, but even then, they were lower than in healthy volunteers. On the other hand, the number of circulating CD146+CD31+ mature endothelial cells were higher than in healthy controls after more than a one-year follow-up. We hypothesize that lower numbers of endothelial precursor cells and higher numbers of endothelial cells in patients undergoing allogeneic haematopoietic stem cell transplantation reflect ongoing endothelial damage, probably caused by immunological mechanisms, and that this longterm damage may explain the higher risk of cardiovascular events in allogeneic haematopoietic stem cell transplant survivors.
Keywords: Endothelial Cells; Adult; transplantace hematopoetických kmenových buněk; Male; lidé; Hematopoietic Stem Cell Transplantation; lidé středního věku; CD antigeny; endoteliální buňky; Humans; kmenové buňky; Middle Aged; homologní transplantace; Young Adult; Antigens, CD; mužské pohlaví; dospělí; Transplantation, Homologous; Stem Cells; mladý dospělý; ženské pohlaví; Female